Inclusions properties at 1673 K and room temperature with Ce addition in SS400 steel - Fei Pan (Nature Portfolio, 2017)
Abstract Inclusion species formed in SS400 steel with Ce-addition was predicted by thermodynamic calculation. The analysis of the inclusion morphology and size distribution was carried out by applying Scanning Electron Microscopy (SEM) and Transmission Electron Microscope (TEM). Nano-Fe3O4 particles were also found in cerium-deoxidized and -desulfurized steel and their shapes were nearly spherical. The complex Ce2O3 inclusions covering a layer of 218 nm composed by several MnS particles with similar diffraction pattern. Most importantly, the complex Ce2O3 characterized by using TEM diffraction is amorphous in the steel, indicating that Ce2O3 formed in the liquid iron and then MnS segregated cling to it.